Psychometric properties of the Portuguese version of the Child Post-Traumatic Cognitions Inventory in a sample of children and adolescents following a wildfire disaster. - Fonseca, Ana (2021)
This study aimed to examine the psychometric properties of the Child Post-Traumatic Cognitions Inventory (CPTCI) in a sample of Portuguese children and adolescents, following the exposition to a wildfire disaster. The sample included 533 children and adolescents living in regions exposed to the wildfire disaster (non-clinical sample: n = 483; clinical sample: n = 50). The short form of the instrument (CPTCI-SF) including two correlated factors (‘Sense of Disturbing and Permanent Change’ and ‘Sense of Being a Fragile Person in a Scary World’) showed good model fit and was invariant across gender and age-groups. Good internal consistency (> .70) was found, and higher CPTCI scores were associated with poorer adjustment indicators. The clinical sample presented significantly higher CPTCI scores than the non-clinical sample. These results contribute to the cross-cultural validation of the CPTCI and support the adequacy of its short form as a reliable and valid measure to be used with Portuguese children and adolescents.